Interceptions and captures of Halyomorpha halys (Hemiptera: Pentatomidae) in Quebec from 2008 to 2018 - Chouinard, Gérald; Larose, Mikael; Légaré, Jean-Philippe; Bourgeois, Gaétan; Racette, Gaétan; Barrette, Maryse (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2018)
The brown marmorated stink bug, Halyomorpha halys (Heteroptera: Pentatomidae), was monitored in southern Quebec through a network of 137 baited pyramid traps deployed in urban and rural habitats between 2014 and 2017. Overall, 73 adults and 9 nymphs were captured. The first capture in rural (an apple orchard) and in urban areas (in Montreal) were observed in 2016. In that same year, 87% of the 54 individuals (adults) caught in Montreal were from a single trap. Similarly in 2017, only two adults were captured in rural habitats and 87% of the 25 captures (16 adults and 9 nymphs) in urban habitats were from the same trap as in 2016. This trap was the only one in which nymphs of various stages were collected, which suggests population establishment in Montreal. Haplotyped specimens from this site (four adults and two nymphs) were all of the H1 haplotype. Over 40 interceptions and sightings by citizens during the period 2008-2018 are also reported.